2008
DOI: 10.1042/bj20080013
|View full text |Cite
|
Sign up to set email alerts
|

Splice-switching efficiency and specificity for oligonucleotides with locked nucleic acid monomers

Abstract: The use of antisense oligonucleotides to modulate splicing patterns has gained increasing attention as a therapeutic platform and, hence, the mechanisms of splice-switching oligonucleotides are of interest. Cells expressing luciferase pre-mRNA interrupted by an aberrantly spliced beta-globin intron, HeLa pLuc705, were used to monitor the splice-switching activity of modified oligonucleotides by detection of the expression of functional luciferase. It was observed that phosphorothioate 2'-O-methyl RNA oligonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…We selected the most efficient SCOs based on the results from the lipofection experiments and assessed their gymnotic activity. Although 186.15-5LNA exhibited good activity, we continued with the similarly efficient 186.15-3LNA, owing to the fact that reduced LNA content potentially could reduce off-target effects (45). Although ZEN-modified SCOs had similar activity compared with the LNA-containing 186.15 versions, they could not be studied, since their availability was limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the most efficient SCOs based on the results from the lipofection experiments and assessed their gymnotic activity. Although 186.15-5LNA exhibited good activity, we continued with the similarly efficient 186.15-3LNA, owing to the fact that reduced LNA content potentially could reduce off-target effects (45). Although ZEN-modified SCOs had similar activity compared with the LNA-containing 186.15 versions, they could not be studied, since their availability was limited.…”
Section: Resultsmentioning
confidence: 99%
“…We modified the selected SCOs with LNA bases, which are known to significantly enhance Tm and increase the efficiency of ONs both in vitro and in vivo (40)(41)(42)(43)(44). More specifically, we chose a 2′OMe RNA backbone with LNA modifications, as this combination has previously demonstrated high potency (45)(46)(47)(48). Since size-reduced SCOs are generally considered to be more efficient (34,42,49), with lowered risk of off-target effects and improved uptake, we designed LNA-modified 15-mer versions of the 186, 187, and 190 series (Supplemental Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…2 0 -O-Methyl RNA containing LNA substitutions has been shown to provide outstanding splice-switching efficiency when used as an antisense agent targeting an aberrantly spliced b-globin intron. 151 Similarly designed oligonucleotides have been used in a steric block strategy to identify RNA-protein binding sites within HIV-1. 152 A variety of sugarmodified analogues have been assessed for their ability to induce RNAse H cleavage, among the worst of the substrates being LNA and a-L-LNA.…”
Section: Oligonucleotides Containing Modified Sugarsmentioning
confidence: 99%
“…We have also shown by UV-T m studies, that the single mismatch discrimination is as high as that shown by OMe-RNA oligomer while forming a duplex with the target RNA and therefore off-target effects might also be less compared with the LNA-OMe mixmer sequences, where sometimes mismatched bases in the target RNA can be tolerated. 20 The oligomer OMe-RNA4-dTSb with 8 additional amino groups, which partially neutralizes the negative charge, was used also in luciferase activity experiments without transfection agent, but no activity was observed (Please see Supplemental Materials). This is perhaps not surprising since there is still a net negative charge in the oligomer.…”
Section: R-ampmentioning
confidence: 99%
“…14,16 It appears that among the plethora of modified AONs currently under evaluation, the promising AONs have some undesirable drawbacks, e.g., phosphorothioate AONs or OMe/LNA mixmers show non-sequence-specific effects due to nonspecific binding to untargeted proteins 19 or due to mismatched non-target recognition as a result of very high duplex stability of AON duplexes with target RNA. 20 The enzyme resistant phosphorothioate AONs are a mixture of diastereomers at every linker phosphorus atom and the separation of diastereomers is not easy. 21 Such AONs also show reduced binding efficiency to RNA.…”
Section: Introductionmentioning
confidence: 99%